Urban planning and regeneration: a community prespective - Brudell, Paula; Hammond, Charlie; Henry, Josephine (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2004)
This article is concerned with one of the key functions and responsibilities exercised by local government - planning, a department whose orientation will have a key role in determining the physical landscape, economy, society and culture of the city. In the case of Dublin, and the local authority with responsibility for Inner Dublin (Dublin City Council), urban geographers have delineated the transformation through which urban planning has undergone in recent decades in response to two key triggers - the introduction of a range of central government urban renewal initiatives and an increasing ethos of entrepreneurialism within the local authority itself. McGuirk and MacLaran (2001) chart the manner in which the local authority has increasingly 'sought refuge in micro-area planning' in response to the marginalisation of their traditional urban planning functions following the introduction of central government's urban renewal programmes (2001 , 437-38) . This programme of centralised renewal initiatives is charted through each of its four stages - the core strategics of which are judged to mirror the emerging culture and pattern of urban entrepreneurialism and regeneration across Europe.
Papers from practice
Keywords: Urban geography -- Ireland